2020
DOI: 10.1038/s41598-020-62355-7
|View full text |Cite
|
Sign up to set email alerts
|

On-board study of gas embolism in marine turtles caught in bottom trawl fisheries in the Atlantic Ocean

Abstract: Decompression sickness (DCS) was first diagnosed in marine turtles in 2014. After capture in net fisheries, animals typically start showing clinical evidence of DCS hours after being hauled on-board, often dying if untreated. these turtles are normally immediately released without any understanding of subsequent clinical problems or outcome. The objectives of this study were to describe early occurrence and severity of gaseous embolism (GE) and DCS in marine turtles after incidental capture in trawl gear, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 23 publications
(42 reference statements)
2
30
2
1
Order By: Relevance
“…We did not nd a correlation between mortality and duration and depth of shing nets, animal size, sex, weight, body temperature, respiratory rate and peripheral edema. Unlike what has been reported recently 20 where PCV was signi cantly lower in turtles that died from GE, we found no statistically signi cant PCV alteration in the turtles that died. However, in about one third turtles analyzed (71/204) we found that PCV was slightly above normal ranges, without any statistical correlations with mortality.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We did not nd a correlation between mortality and duration and depth of shing nets, animal size, sex, weight, body temperature, respiratory rate and peripheral edema. Unlike what has been reported recently 20 where PCV was signi cantly lower in turtles that died from GE, we found no statistically signi cant PCV alteration in the turtles that died. However, in about one third turtles analyzed (71/204) we found that PCV was slightly above normal ranges, without any statistical correlations with mortality.…”
Section: Discussioncontrasting
confidence: 99%
“…These turtles died during hospitalization in a time comparable to that observed in our study. In a recent study 20 12 of 28 (43%) animals died onboard shing vessels and 3 of 15 (20%) turtles released with satellite tags died within 6 days. About 90% turtles with GE alive upon arrival at STC recovered from the disease in a time ranging from 1 and 13 days without any supportive drug therapy.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations